Non-symmetric flow over a stretching/shrinking surface with mass transfer - Lok, Yian Yian; Merkin, John H.; Pop, Ioan (Mathematical Modelling and Analysis, 2019)
The non-symmetric flow over a stretching/shrinking surface in an otherwise quiescent fluid is considered under the assumption that the surface can stretch or shrink in one direction and stretch in a direction perpendicular to this. The problem is reduced to similarity form, being described by two dimensionless parameters, γ the relative stretching/shrinking rate and S characterizing the fluid transfer through the boundary. Numerical solutions are obtained for representative values of γ and S, a feature of which are the existence of critical values  of γ dependent on S, these being determined numerically. Asymptotic forms for large γ and S, for both fluid withdrawal, S > 0 and injection S < 0 are obtained and compared with the corresponding numerical results.